2014
DOI: 10.1016/j.jmb.2013.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of an Ectodomain Motif in the Influenza A Virus Neuraminidase Alters Tetherin Sensitivity and Results in Virus Attenuation In Vivo

Abstract: SUMMARY We previously demonstrated that ectodomain residue Asp286 in N2 neuraminidase (NA; Asp268 in N1 NA) present in budding-capable NA proteins contributes to productive NA plasma membrane transport partly by mediating escape from tetherin restriction1. Budding-incapable NA proteins contain a G at this position and either co-expression of HIV-1 vpu, or siRNA-mediated depletion of tetherin rescued budding capabilities in these proteins1. Furthermore, replacement of D286 with G in budding-capable NA proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…In this study, we prove that the glycosites in the stalk domain of NA are glycosylated to regulate the activity, affinity, and specificity of NA to modulate IAV replication, suggesting that the glycans in the stalk domain of NA play an important role in the virulence and transmission of IAV. However, the relationship between NA activity and the diversity of the stalk domain, and whether the virus release is regulated by the glycosylation in the stalk domain is still unknown (24,25). Our study here revealed that NA glycosylation is important for IAV virulence and transmission.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, we prove that the glycosites in the stalk domain of NA are glycosylated to regulate the activity, affinity, and specificity of NA to modulate IAV replication, suggesting that the glycans in the stalk domain of NA play an important role in the virulence and transmission of IAV. However, the relationship between NA activity and the diversity of the stalk domain, and whether the virus release is regulated by the glycosylation in the stalk domain is still unknown (24,25). Our study here revealed that NA glycosylation is important for IAV virulence and transmission.…”
Section: Discussionmentioning
confidence: 62%
“…Studies employing FLUAV VLP systems provided evidence that release of FLUAV-like particles can be restricted by tetherin (18,23), although some viral NAs counteract tetherin with modest efficiency (20,21,23), potentially by altering tetherin glycosylation (21). However, these studies did not examine HA and NA jointly for tetherin antagonism and/or did not analyze HA and NA proteins from pandemic FLUAV.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies indicated that FLUAV is only inefficiently inhibited by tetherin or is completely tetherin insensitive (17)(18)(19), while release of FLUAV-like particles is inhibited by tetherin (18). In contrast, subsequent analyses demonstrated appreciable inhibition of FLUAV release by tetherin (20)(21)(22). In addition, evidence for a tetherin-antagonizing activity of certain neuraminidase (NA) proteins was reported (20,23), but the antagonism is believed to be relatively inefficient (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contradictory reports soon emerged, however, of viruses inherently sensitive to BST-2 restriction (Gnirss et al, 2015;Hu et al, 2017;Mangeat et al, 2012). Differential abilities of various influenza virus neuraminidases (NA) in circumventing BST-2 activity (Leyva-Grado et al, 2014;Yondola et al, 2011) made it apparent that influenza virus sensitivity to BST-2 is likely to be strain-specific. Further studies supported the possibility that influenza virus NA acts a strainspecific antagonist to BST-2 (Leyva-Grado et al, 2014;Mangeat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%